Faktor-Faktor yang Mempengaruhi Kecemasan Mahasiswa dalam Menghadapi Praktik Klinik Keperawatan - Ramadhan Trybahari Sugiharno; Wibowo Hanafi Ari Susanto; Ardiansa Ardiansa; Frengki Wospakrik; Ester Ester (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to look at the factors that influence student anxiety in facing clinical nursing practice. This research is a quantitative study using a cross-sectional study design approach. The results showed that the majority of respondents (69.14%) were female, 56 people, and most of the 39 respondents (48.1%) of all respondents had moderate anxiety. In addition, 51 respondents (63%) had good knowledge, up to 52 respondents (64.2%) had good skills, 61 respondents (75.3%) had significant supervisory influence, and 46 respondents (56.8% ) had an excellent environmental effect. In conclusion, there is an important relationship between knowledge, skills, supervisors, and the environment with students' anxiety in facing clinical nursing practice. Keywords: Anxiety, Nursing, Students, Clinical Practice